2019
DOI: 10.1007/s10237-018-01106-0
|View full text |Cite
|
Sign up to set email alerts
|

Lateral impacts correlate with falx cerebri displacement and corpus callosum trauma in sports-related concussions

Abstract: Corpus callosum trauma has long been implicated in mild traumatic brain injury (mTBI), yet the mechanism by which forces penetrate this structure is unknown. We investigated the hypothesis that coronal and horizontal rotations produce motion of the falx cerebri that damages the corpus callosum. We analyzed previously published head kinematics of 115 sports impacts (2 diagnosed mTBI) measured with instrumented mouthguards and used finite element (FE) simulations to correlate falx displacement with corpus callos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 64 publications
(101 reference statements)
5
60
1
Order By: Relevance
“…In other words, the Von Mises stress decreases the closer CC is to the free edge of the FC. This trend seems to contradict the conclusion of Hernandez et al (2019) who showed that the strain in the CC decreased (from 0.37 to 0.17) in simulations without taking the FC into account. Nevertheless, FC is a rigid element in the centre of the cranial cavity that limits lateral movement of the brain; without it, the CC is free to move and is then less stressed.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…In other words, the Von Mises stress decreases the closer CC is to the free edge of the FC. This trend seems to contradict the conclusion of Hernandez et al (2019) who showed that the strain in the CC decreased (from 0.37 to 0.17) in simulations without taking the FC into account. Nevertheless, FC is a rigid element in the centre of the cranial cavity that limits lateral movement of the brain; without it, the CC is free to move and is then less stressed.…”
Section: Resultscontrasting
confidence: 67%
“…On impact, mechanical loading of the corpus callosum was shown to be strongly associated with the occurrence of concussion (Jang et al 2019). In addition, a recent study based on finite element simulation of lateral impacts on the head, has demonstrated the influence of the interaction between the falx cerebri and the corpus callosum on its mechanical loading (Hernandez et al 2019). However, the relationship between this local anatomy and these mechanical loads has not yet been analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature from finite element modelling of head impacts support these findings in showing that the CC is relatively tethered by the anatomy of the falx cerebri ( Hernandez et al , 2019 ), which may affect the direct transfer of rotational forces to the tissues, and induce more shearing injury of the WM fibre tract. Although the central attachment of the falx may provide some structural stability, differences in fibre compositions (i.e.…”
Section: Discussionmentioning
confidence: 85%
“…In recent years, advances in computational modelling of head injuries have identified the corpus callosum (CC) as a fibre tract with high injury susceptibility ( McAllister et al , 2012 ; Stamm et al , 2015 ; Hernandez et al , 2019 ). As the largest commissural fibre tract in the brain, the density and fibre orientation of the CC appear to make this WM tract more vulnerable to diffuse axonal injury ( Johnson et al , 2012 ; McAllister et al , 2012 ; Beckwith et al , 2018 ; Hernandez et al , 2019 ), due to the increased shear forces transferred locally, upon exposure to external acceleration/deceleration forces. Preliminary evidence from impact biomechanics ( McAllister et al , 2012 ; Hernandez et al , 2019 ) suggests that differences in sub-structures within the anatomy of the CC, along with heterogeneity in the deformation fields induced from mechanical loading, may contribute to the increased susceptibility of the CC for changes in WM integrity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation